The Effect of Entrepreneurial Orientation on Melinjo Processing Industries in Batang Regency - Intan Adhitya Rosmasari; Siti Jahroh; Budi Purwanto (School of Business, IPB University (SB-IPB), 2019)
Micro, small and medium enterprises play an important role in improving the people’s economy. The contribution of small enterprises can increase state income, absorb labor, improve welfare evenly, and stimulate people’s economy by leading to the entrepreneurial orientation to support better business performance. The purposes of the study were to find out the effect of entrepreneurial orientation on business performance and the effect of entrepreneurial characteristic on entrepreneurial orientation and performance. The respondents were taken from 60 independent entrepreneurs and KWT Tani rejo of the melinjo chips processing industry in Batang Regency. The data were analyzed using Partial Least square (PLS) approach. The results showed that entrepreneurial characteristic influenced entrepreneurial orientation and business performance. In addition, entrepreneurial orientation had a positive effect on the performance of melinjo chips processing business. Entrepreneurs who implement entrepreneurial orientation from innovativeness, proactiveness, competitive aggressiveness, risk-taking and power of autonomy side will have a good impact on their business performance.Keywords: MSMEs, entrepreneurial characteristic, entrepreneurial orientation, business performance, PLS